2020
DOI: 10.1155/2020/2164685
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation and Measure of Accuracy of ELISAs, CLIAs, and ECLIAs for the Detection of HIV Infection among Blood Donors in China

Abstract: Background. Enzyme-linked immunosorbent assay (ELISA) is the only serological method approved for blood screening in China. Automated chemiluminescence immunoassay (CLIA) and electrochemiluminescence immunoassay (ECLIA) had been used in clinical laboratories but not applied to screen HIV among blood donors. This study aimed to evaluate the performance of ELISA, CLIA, and ECLIA, focusing on the feasibility of CLIA/ECLIA for blood screening. Method. 1029 blood donations from 14 blood centers screened by ELISA we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Both ELISA and CLIA were more specific and accurate [12] Comparison of CLIA, ELISA and passive agglutination for diagnosis of Mycoplasma pneumoniae infection.…”
Section: Research Title Results Referencesmentioning
confidence: 98%
“…Both ELISA and CLIA were more specific and accurate [12] Comparison of CLIA, ELISA and passive agglutination for diagnosis of Mycoplasma pneumoniae infection.…”
Section: Research Title Results Referencesmentioning
confidence: 98%
“…Unlike IgG antibody and total antibody tests, IgM antibody and IgA antibody tests generally have a specificity of less than 99 percent [ 16 ]. The anti-N and anti-S tests used in our study work with the ECLIA method and can be considered reliable since they show high sensitivity and specificity rates and a relatively narrow confidence interval [ 11 , 15 , 16 ]. Regarding the COVID-19 antibody tests, the Infectious Diseases Society of America (IDSA) recommends using IgG only or total antibody tests since their accuracy is higher, instead of IgM only or IgA only tests [ 10 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…quantification, could be one of the causes of these discrepancies. In general, it has been reported that CLIA has higher specificity and accuracy than quantitative methods such as ELISA and agglutinin for the detection of many viruses [19][20][21]. The quantitative values calculated by automated chemiluminescence instruments could be more consistent and wider than those measured by ELISA in earlier studies and would achieve a better correlation with clinical features.…”
Section: Plos Onementioning
confidence: 95%
“…For all specimens, 0.3 mL was aliquoted into microtubes and stored at -70˚C before testing. The median number of samples per patient was 6.0 (95% CI = 3.35-6.0), and the median follow-up period was 17 days (95% CI = [15][16][17][18][19][20][21]. This study was approved by the Institutional Review Board (IRB) of Kangnam Sacred Heart Hospital of Hallym University (IRB No.…”
Section: Patientsmentioning
confidence: 99%